Optimizing acceptability and feasibility of an evidence-based behavioral intervention for obese adults with obesity-related co-morbidities or additional risk factors for co-morbidities: an open-pilot intervention study in secondary care. - Dombrowski SU; Sniehotta FF; Johnston M; Broom I; Kulkarni U; Brown J; Murray L; Araújo-Soares V; Dombrowski, Stephan U; Sniehotta, Falko F; Johnston, Marie; Broom, Iain; et al. (Patient Education & Counseling, 2012)
Objective: To test and optimize the feasibility and acceptability of a physical activity (PA) and healthy eating behavior change intervention for obese adults with obesity-related co-morbidities or additional risk factors for co-morbidities.Methods: Open-pilot intervention study using an uncontrolled pre and post design with ongoing measures on intervention acceptability and feasibility. Participants received 5 weekly nurse-led one-hour long group sessions. Acceptability and feasibility were assessed throughout. PA, dietary behavior and weight were measured before and after the intervention.Results: Of 74 consenting participants, 61 (82%) received and 47 (64%) completed the intervention. Average ratings of intervention materials and components by participants ranged between 4.1 and 4.9 out of 5. Average facilitator satisfaction rating was 90% (range 75-100%). The intervention delivery was feasible as indicated by ratings and comments from participants and the facilitator. Participants lost -0.86 kg of weight t(45)=3.84, p=0.0001, and increased PA by an additional 1.6 (SD=2.7) sessions/week, t(31)=-3.3, p=0.002. No significant dietary differences emerged.Conclusion: The intervention was acceptable to the facilitator and participants and feasible for delivery. Several intervention aspects were further optimized.Practice Implications: The current study outlines a PA and dietary behavior change pilot intervention coupled with a systematic and transparent process of intervention optimization.